2015
DOI: 10.4028/www.scientific.net/jnanor.32.93
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Gold Nanoparticle Biosynthesis by <i>Es</i><i>cherichia</i> <i>co</i><i>li</i> DH5α and its Conjugation with Gentamicin

Abstract: Metal nanoparticles are one option for targeted drug delivery. In order to increase antibiotic efficiency and decrease its side effects, antibiotic conjugated nanoparticles have been known as a suitable approach. The aim of this study was optimization of gold nanoparticle biosynthesis byEscherichia coliDH5α and its conjugation with gentamicin. For this purpose gold nanoparticles were biosynthesized from HAuCl4and confirmed by Uv/ Vis, XRD, DLS and SEM. Then the effects of different parameters on optimum condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Hence, the ideal bone cement should provide antimicrobial activity for an extended period of time in order to exhibit a prophylactic action against late infection offset; this could be achieved through the application of drug delivery systems . For this purpose, antibiotic delivery systems have been prepared through various techniques, for example, tethering the drug to a surface or to a particle, encapsulating the active molecule in nanoparticles or liposomes or depositing the drug using layer-by-layer (LbL) assembly. , Such multitude of approaches demonstrates the clear clinical need of an antimicrobial delivery system for bone cement; however, it also reveals the still unsatisfactory performance of the available approaches. For example, the entrapment of an antibiotic in mesoporous silica coated with hydrolyzable polymers suffers the trade-off between an extended efficacy and immediate release; in order to extend the release, thicker coatings are required, but this, in turn, prevents release in the first hours/days of contact with fluids .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the ideal bone cement should provide antimicrobial activity for an extended period of time in order to exhibit a prophylactic action against late infection offset; this could be achieved through the application of drug delivery systems . For this purpose, antibiotic delivery systems have been prepared through various techniques, for example, tethering the drug to a surface or to a particle, encapsulating the active molecule in nanoparticles or liposomes or depositing the drug using layer-by-layer (LbL) assembly. , Such multitude of approaches demonstrates the clear clinical need of an antimicrobial delivery system for bone cement; however, it also reveals the still unsatisfactory performance of the available approaches. For example, the entrapment of an antibiotic in mesoporous silica coated with hydrolyzable polymers suffers the trade-off between an extended efficacy and immediate release; in order to extend the release, thicker coatings are required, but this, in turn, prevents release in the first hours/days of contact with fluids .…”
Section: Introductionmentioning
confidence: 99%
“…Motamedi et al . showed that conjugation of GTM with GNPs can facilitate antibiotic penetration towards bacterial cells [14], as GTM alone does not cross cell membranes efficiently [13]. Depending on the antibiotic used, an increase in the activity of the antibiotic–colloidal‐gold mixture ranged from 12 to 40%, as compared with the activities of the native drugs [13].…”
Section: Introductionmentioning
confidence: 99%